Spare parts : the story of medicine through the history of transplant surgery - Craddock, Paul (PhD) (St. Martin's Press, 2022)
"We think of transplant surgery as one of the medical wonders of the modern world but it's a lot older than you think. As ancient as the pyramids, its history is even more surprising. Cultural historian Paul Craddock takes us on a journey - from sixteenth-century skin grafting to contemporary stem cell transplants - uncovering stories of experiments and operations performed by unexpected people in unexpected places. Bringing together philosophy, science and cultural history, Spare Parts explores how transplant surgery constantly tested the boundaries between human, animal and machine. It shows us that the history - and future - of transplant surgery is tied up with questions not only about who we are, but also what we are, and what we might become"--Publisher's description.